Wind Power Generation in India: Evolution, Trends and Prospects - Khan, M.F.; Khan, M.R. (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
In the present context of shrinking conventional resources coupled with environmental perils, the wind power offers an attractive alternative. Wind power generation in India started way back in early 1980s with the installation of experimental wind turbines in western and southern states of Gujarat and Tamil Nadu. For first two decades of its existence until about 2000 the progress was slow but steady. In last one decade Indian wind electricity sector has grown at very rapid pace which has promoted the country to the fifth position as largest wind electric power generator and the third largest market in the world. The galvanization of wind sector has been achieved through some aggressive policy mechanisms and persistent support by government organizations such as MNRE and C-WET. This paper articulates the journey of Indian wind program right since its inception to the present trends and developments as well as the future prospects.Â